Fronto-temporal Lobe Epilepsy Presenting as Intermittent Outburst of Anger: A Case Report from Eastern Nepal - Acharya, Neeraj; Nayak, Sonali; Nepal, Suraj; Shah, Bhupendra (Journal of Psychiatrists’ Association of Nepal, 2021)
Episodes of rage and anger with violent outbursts are common manifestations of various psychiatric and behavioral disorders. Though rare, it can be a manifestation of fronto-temporal lobe epilepsy which is often misdiagnosed. Here we present a case of 20 years male having intermittent episodes of anger and violent outburst for three years who was later diagnosed as a case of fronto-temporal lobe epilepsy.